2016
DOI: 10.1108/mf-12-2014-0300
|View full text |Cite
|
Sign up to set email alerts
|

Financial integration and diversification benefits: China and ASEAN4 countries

Abstract: Purpose – The strategic partnership between China and ASEAN has resulted in significant financial reforms at the country and regional level. The scale and pace of these changes call for systematic assessments of their bearing on the development and integration of financial markets in this region. The purpose of this paper is to investigate the level of financial integration of the equity markets in China and ASEAN4 countries (Indonesia, Malaysia, Philippines, and Thailand) for the period 2004-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…As for the daily returns, the study concluded that China's market correlation with other five emerging Asian markets including Malaysia is much higher compared to that of Australia and the USA. A similar result was also found by Nguyen and Elisabeta (2016) indicating that the level of financial integration across China and four ASEAN equity markets (Indonesia, Malaysia, Philippines and Thailand) increased significantly during the financial crisis period. Meanwhile, Christoffersen et al (2012Christoffersen et al ( , 2014 who investigated the correlations of weekly returns for 16 developed markets such as Australia, France, Germany, Japan, the UK and the USA and several emerging markets including Malaysia over the period January 12, 1973, to June 12, 2009, and January 12, 1973, to December 28, 2012, respectively, using several econometric models including dynamic conditional copula approach, BEKK, DCC and DECO, found that the level of diversification benefits offered by the emerging markets is still quite high.…”
Section: International Portfolio Diversification Benefitsupporting
confidence: 80%
“…As for the daily returns, the study concluded that China's market correlation with other five emerging Asian markets including Malaysia is much higher compared to that of Australia and the USA. A similar result was also found by Nguyen and Elisabeta (2016) indicating that the level of financial integration across China and four ASEAN equity markets (Indonesia, Malaysia, Philippines and Thailand) increased significantly during the financial crisis period. Meanwhile, Christoffersen et al (2012Christoffersen et al ( , 2014 who investigated the correlations of weekly returns for 16 developed markets such as Australia, France, Germany, Japan, the UK and the USA and several emerging markets including Malaysia over the period January 12, 1973, to June 12, 2009, and January 12, 1973, to December 28, 2012, respectively, using several econometric models including dynamic conditional copula approach, BEKK, DCC and DECO, found that the level of diversification benefits offered by the emerging markets is still quite high.…”
Section: International Portfolio Diversification Benefitsupporting
confidence: 80%
“…Chiang and Chen (2016) found the highest correlation of China with Hong Kong, followed by Taiwan and Korea, and low correlation between Europe and the USA. Nguyen and Elisabeta (2016) investigated the integration among China and Association of South East Asian Nations' (ASEAN) stock as well as the sectoral market (consumer goods, financial, industrial, Properties and real estate) by employing the DCC-MGARCH model with a discrete wavelet transformation (DWT), and Paramati, Roca, and Gupta (2016) investigated integration and dynamic linkage in 10 Asian markets over 13 years of weekly observations through co-integration, ADCC and panel regression models and found increasing economic integration both in the short and in the long run among the sample markets during the study period. Rehman (2017) examined the time-varying co-movements of Japanese stock markets with selected economic fundamentals (such as implied volatility index, policy uncertainty index, oil price, exchange rate and inflation) and reported a significant impact of exchange rate and oil price changes on the time-varying correlation between implied volatility index and stock market returns.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Keterkaitan antar bursa ini disebut Contagion Effect yaitu kondisi suatu bursa akan mempengaruhi bursa yang lain dimana bursa yang lebih besar akan mempengaruhi bursa yang lebih kecil. Integrasi antar pasar saham Asia maupun secara global telah terbukti dari hasil penelitian (Mohti, Dionísio, Vieira, & Ferreira, 2019), (Karim & Majid, 2010), (Arsyad, 2015), (Boubakri & Guillaumin, 2015), (Dhanaraj, Gopalaswamy, & Babu M, 2013), (Hooy & Lim, 2013), (Lee, 2019), (Mukherjee & Mishra, 2010), (Narayan, Sriananthakumar, & Islam, 2014), (Nguyen & Elisabeta, 2016), (Shegorika Rajwani Jaydeep Mukherjee, 2013).…”
Section: Pendahuluanunclassified